2012
DOI: 10.7326/0003-4819-156-5-201203060-00005
|View full text |Cite
|
Sign up to set email alerts
|

Do Physicians Understand Cancer Screening Statistics? A National Survey of Primary Care Physicians in the United States

Abstract: Background: Unlike reduced mortality rates, improved survival rates and increased early detection do not prove that cancer screening tests save lives. Nevertheless, these 2 statistics are often used to promote screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
190
0
13

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 252 publications
(210 citation statements)
references
References 23 publications
7
190
0
13
Order By: Relevance
“…Some have proposed that in preference-sensitive decisions, patients need exact probabilities of harms and benefits associated with each option to appropriately weigh the pros and cons of each; 6 however, these probabilities are often not available in EM, and even when they are, both patients and physicians may be limited by the inherent challenges of effective risk communication. [10][11][12][13][14] Finally, patients who are potentially critically ill may prefer that clinicians take a more dominant role in decision-making. [15][16][17][18] Despite nationwide efforts and focus on patient-centeredness, viewpoints of frontline practicing clinicians on how practically to achieve increased patient engagement remain largely unknown.…”
mentioning
confidence: 99%
“…Some have proposed that in preference-sensitive decisions, patients need exact probabilities of harms and benefits associated with each option to appropriately weigh the pros and cons of each; 6 however, these probabilities are often not available in EM, and even when they are, both patients and physicians may be limited by the inherent challenges of effective risk communication. [10][11][12][13][14] Finally, patients who are potentially critically ill may prefer that clinicians take a more dominant role in decision-making. [15][16][17][18] Despite nationwide efforts and focus on patient-centeredness, viewpoints of frontline practicing clinicians on how practically to achieve increased patient engagement remain largely unknown.…”
mentioning
confidence: 99%
“…3 The dismissive tone of the article by Woloshin and Schwartz 1 is in contrast to another recent article on drug treatment of obesity, which noted that the new drugs may be useful adjuncts to lifestyle treatment for carefully selected patients. 4 Bias against people with obesity, even from physicians, is well documented.…”
Section: Drug Treatment Of Obesitymentioning
confidence: 96%
“…Studies have shown that even those who have high fundamental literacy skills have poor health literacy and that up to half of US adults are not able to effectively use written material to accomplish healthrelated tasks. 3 The practice of medicine is dynamic with constant shifts to diagnostic and treatment paradigms. The exponential growth of medical knowledge adds to the complexity of medical care, and there is the concern that physicians have difficulties accurately interpreting and translating evidence into clinical practice.…”
mentioning
confidence: 99%
See 2 more Smart Citations